Realizing near-UV light excitation of Mn2+ via efficient energy transfer from Eu2+ for white LEDs. (May 2020) - Dong, Quan; Yang, Jiaojie; He, Shengan; Cui, Jun; Yang, Fengli; Peng, Jiaqing; Du, Fu; Yang, Shaohua; Ye, Xinyu
Graphical abstract: Highlights: The highest energy transfer efficiency of Eu 2+ → Mn 2+ can achieve about 78 %. The integrated emission intensity of Al5 O6 N:Eu 2+, Mn 2+ at 150 ℃ can maintain 82 %. The tunable color emission of the samples can be realized tuned from blue to green. Abstract: A series of Eu 2+ and Mn 2+ co-activated Al5 O6 N multi-color phosphors were fabricated through the gas-pressure sintering method, and they displayed intense blue-green emitting at near-ultraviolet irradiation due to efficient energy transfer. Dipole-dipole interaction was proved to be the leading role for Eu 2+ -Mn 2+ energy transfer and the highest energy transfer efficiency was obtained about 78 %. Furthermore, tunable emissions from blue to green were observed through regulating the concentration of Eu 2+ and Mn 2+ . In addition, the temperature-dependent luminescence behavior of Al5 O6 N:Eu 2+, Mn 2+ was examined, and the emission intensity at 150℃ maintains 82 % of initial intensity, which indicates superior thermal stability. These outcomes illustrate that the Al5 O6 N: Eu 2+, Mn 2+ phosphors may be potentially used in white LEDs.